Male Ejaculatory Endophenotypes: Revealing Internal Inconsistencies of the Concept in Heterosexual Copulating Rats - Trejo-Sánchez, Itztli; Pérez-Monter, Carlos; Huerta-Pacheco, Sofía; Gutiérrez-Ospina, Gabriel (Frontiers in Behavioral Neuroscience, 2020)
Distinct manifestations of sexual behavior are conceived as separate phenotypes. Each sexual phenotype is assumed to be associated with a characteristic brain. These notions have justified the phenotyping of heterosexual copulator males based upon their ejaculation’s latencies (EL) or frequencies (i.e., cumulative ejaculation number; EN). For instance, men and male rats showing premature, normal or retarded ejaculation are assumed to be distinctive endophenotypes. This concept, nonetheless, contradicts past and recent evidence that supports that sexual behavior is highly variable within each sex, and that the brain sexual functional morphology represents an intricate sexual phenotypic mosaic. Hence, for ejaculatory male endophenotypes to be considered as a valid biological concept, it must show internal consistency at various levels of organization (including genetic architectures), after being challenged by intrinsic and/or extrinsic factors. We then judged the internal consistency of the presumed ejaculatory endophenotypes by assessing whether copulatory behavior and the expression of copulation relevant genes and brain limbic structures are specific to each of the presumed EL- or EN-ejaculatory endophenotypes. To do this, copulating male rats were first phenotyped in groups consistently displaying short, average or long ejaculation latencies or very high, high, average, low or very low EN, based in their copulatory performance. Then, the internal consistency of the presumed EL- or EN-endophenotypes was tested by introducing as covariates of phenotyping other copulatory parameters (e.g., number of intromissions) in addition to EL or EN, or by analyzing the expression levels of genes encoding for estrogen receptor alpha, progesterone receptor, androgen receptor, aromatase, DNA methyl-transferase 3a and DNA methyl-transferase 1 in the amygdala, medial preoptic area, ventromedial hypothalamus and olfactory bulb. We found that even though there were group-level differences in all the variables that were studied, these differences did not add-up to create the presumed EL- or EN-ejaculatory endophenotypes. In fact, the extensive overlapping of copulatory parameters and expression levels of copulation relevant genes in limbic structures across EL- or EN-phenotyped copulating male rats, is not consistent with the hypothesis that distinct ejaculatory endophenotypes exist and that they are associated with specific brain characteristics.